Induction of UV-B Stress Tolerance by Momilactones and Gibberellic Acid in Rice - Ramin Rayee; La Hoang Anh; Tran Dang Xuan (Crops)
This study aims to investigate the effects of momilactone-rich bran fractions (MRBF) and gibberellic acid (GA3) on the physiological responses, biochemical composition, and antioxidant activity in rice (Oryza sativa L.) under UV-B stress. Rice seedlings were treated with MRBF (3 mg mL−1), or GA3 (50 and 100 µM) by foliar spraying, then exposed to UV-B-induced stress for 0, 1.5, and 3 h. Phenolic acids and endogenous momilactones A (MB) and B (MB) were analyzed using high-performance liquid chromatography (HPLC) and ultra-performance liquid chromatography–electrospray ionization–mass spectrometry (UPLC-ESI-MS). The results demonstrated that UV-B stress reduced chlorophyll and carotenoid, which were significantly elevated by GA3 and GA3 + MRBF treatments. MRBF alone increased proline concentrations by 18.33%, while GA3 significantly enhanced total flavonoid content (TFC), and GA3 + MRBF raised total phenolic content (TPC). Among identified phenolic acids, sinapic, ferulic, and salicylic acids were notably elevated under MRBF and 3 h UV-B stress, while cinnamic and gallic acids were markedly reduced. The highest endogenous MA content was found in MRBF-treated plants under 1.5 h UV-B stress, with significant MA and MB concentrations also in plants treated with 50 µM GA3 + MRBF after extended UV-B exposure. This combination also enhanced antioxidant activities and reduced rice seedlings’ oxidative stress index (OSI) by 30.55%. Correlation analysis showed a significant relationship of MA with TPC and proline. Together, these results support the potential role of momilactones in regulating UV-B stress tolerance in rice; however, the molecular mechanisms underlying this regulation require further investigation.